2012
DOI: 10.3109/03009734.2011.653606
|View full text |Cite
|
Sign up to set email alerts
|

The interface between inhibition of descending noradrenergic pain control pathways and negative affects in post-traumatic pain patients

Abstract: BackgroundAnimal studies have shown that surgical trauma activates the descending noradrenergic pathway. However, perioperative patients have decreased concentrations of noradrenaline (NA) in the cerebrospinal fluid (CSF). We proposed that the descending monoaminergic pathway is altered in post-traumatic pain patients and that CSF monoamine neurotransmitters may be more closely related to affective symptoms. We investigated the levels of monoamine neurotransmitters and assessed pain in these patients.MethodsPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The latter could indicate sustained activation of the descending noradrenergic inhibitory pain pathway up to d 1-8, followed by fatigue of the same pathway. This was in line with previous studies that reported decreased CSF noradrenaline release following traumatic pain in patients (Cui et al, 2012). Nevertheless, CSF noradrenaline was a moderately effective pain biomarker because it did not differentiate between the 3 expected levels of analgesia.…”
Section: Discussionsupporting
confidence: 91%
“…The latter could indicate sustained activation of the descending noradrenergic inhibitory pain pathway up to d 1-8, followed by fatigue of the same pathway. This was in line with previous studies that reported decreased CSF noradrenaline release following traumatic pain in patients (Cui et al, 2012). Nevertheless, CSF noradrenaline was a moderately effective pain biomarker because it did not differentiate between the 3 expected levels of analgesia.…”
Section: Discussionsupporting
confidence: 91%
“…It should be noted that this study showed no significant difference in CSF noradrenaline levels between the control and labor pain groups. In contrast, previous studies reported CSF noradrenaline level to be significantly decreased in patients with posttraumatic pain [ 8 ] and postsurgical pain [ 10 ], both of which are somatic pain. These findings make us question whether or not the descending noradrenergic pathways underlying the pain mechanisms of visceral pain and somatic pain are different.…”
Section: Discussionmentioning
confidence: 72%
“…In the present study, there was a significant decrease in CSF serotonin concentration in parturients with severe labor pain. Previous studies reported significant increase in CSF serotonin in pregnant women with painful active labor [visual analogue scale of 6.2 (IQR 4.8–7.6)]; however, the severity of pain was not intense [ 8 ]. It appears evident that the high level of pain intensity (NRS = 9) and the median pain duration of 325 minutes (5.4 hours) in the labor pain group in this study was sufficient to influence descending serotonergic control since an inverse correlation was observed between pain intensity and CSF serotonin level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations